2011
DOI: 10.1128/iai.05647-11
|View full text |Cite
|
Sign up to set email alerts
|

Infection Intensity-Dependent Responses of Anopheles gambiae to the African Malaria Parasite Plasmodium falciparum

Abstract: Malaria remains a devastating disease despite efforts at control and prevention. Extensive studies using mostly rodent infection models reveal that successful Plasmodium parasite transmission by the African mosquito vector Anopheles gambiae depends on finely tuned vector-parasite interactions. Here we investigate the transcriptional response of A. gambiae to geographically related Plasmodium falciparum populations at various infection intensities and different infection stages. These responses are compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 30 publications
6
61
0
Order By: Relevance
“…These results are consistent with previous gene expression analysis for LL3 [19], and are remarkably similar to the patterns of SRPN6 expression identified in previous experiments [9] and in this report. Consistent with these results, immunolocalization experiments imply that LL3 expression occurs in cells of the midgut epithelium in close proximity to invading ookinetes.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous gene expression analysis for LL3 [19], and are remarkably similar to the patterns of SRPN6 expression identified in previous experiments [9] and in this report. Consistent with these results, immunolocalization experiments imply that LL3 expression occurs in cells of the midgut epithelium in close proximity to invading ookinetes.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, P. falciparum and P. berghei infection of the mosquito midgut occur with different timing and at different temperatures. In that respect, published data suggest that PGRPLA1 and PGRPLA2 expression differs between mosquito strains and Plasmodium infection stages [21][22][23][24] , and we found that PGRPLA2 expression is 14 and 10 times lower than that of PGRPLA1 in the midguts of sugar-and blood-fed mosquitoes of our colony, respectively. Moreover, as mentioned in the results, the observed phenotypic difference may arise from PGRPLA1 dsRNA having a higher silencing efficiency and being less isoform specific than PGRPLA2 dsRNA.…”
Section: Discussionmentioning
confidence: 62%
“…Only a modest increase was observed in one of the replicates at 12 hpi but, in another, the expression was lower after infection than in the uninfected control. Although activation of the JNK pathway involves a cascade of post-translational phosphorylation events, transcription of JNK pathway members has been reported to increase upon Plasmodium infection in Anopheles and transcriptional activation of JNK at the mRNA and protein level has also been observed in Drosophila midguts in response to bacterial challenge [26][28]. JNK protein expression was also induced in the mosquito midgut in response to Plasmodium infection (Figure S1).…”
Section: Resultsmentioning
confidence: 97%